Does parental drinking influence children's drinking? A systematic review of prospective cohort studies. (16th October 2015) - Rossow, Ingeborg; Keating, Patrick; Felix, Lambert; McCambridge, Jim
Abstract: Aims: To evaluate evidence of the capacity for causal inference in studies of associations between parental and offspring alcohol consumption in the general population. Methods: A systematic search for, and narrative analysis of, prospective cohort studies of the consequences of drinking, except where assessed prenatally only, or with clinically derived instruments. Primary outcome measures were alcohol use or related problems in offspring, which were collected at least 3 years after exposure measures of parental drinking. The systematic review included 21 studies comprising 26 354 families or parent–child dyads with quantitative effect measures available for each study. Criteria for capacity of causal inference included (1) theory‐driven approach and analysis; (2) analytical rigour; and (3) minimization of sources of bias. Results: Four of the 21 included studies filled several, but not all, criteria and were assessed to have some capacity for causal inference. These four studies found some evidence that parental drinking predicted drinking behaviour in adolescent offspring. The remaining 17 studies had little or no such capacity. Conclusions: There is a fairly large and consistent literature demonstrating that more parental drinking is associated with more drinking in offspring. Despite this, existing evidence is insufficient to warrant causal inferences at this stage.